Mengembalikan Kejayaan Pasar Tanah Abang Di Era Pandemi Melalui Peningkatan Kinerja Para Pedagang (UMKM) - Raden Ajeng Entaresmen; Farah Margaretha; Henik Hari Astuti; Gusti Dia Karima; Putri ufiandah (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta (BPJP - STEI), 2022)
Micro, Small and Medium Enterprises (MSMEs) from time to time have increased. The business people also produce various types of products. MSMEs are one of the breakthroughs in increasing economic growth in the midst of society to achieve adequate living welfare. MSMEs are the pillars of the Indonesian economy, because they help the community's economic growth. Community independence is like business people. This MSME is expected to be able to reduce the unemployment rate if you look at the fact that employment opportunities are increasingly limited and the number of workers who have not been absorbed continues to grow. The main problems of MSMEs today are mainly related to difficulties in terms of marketing and financial management. As well as the lack of various trainings in terms of marketing their products and simple financial management methods for MSME actors, so as to improve welfare for MSME actors with sharia concepts. The problem can be formulated, how to improve the welfare of SMEs with the concept of sharia. The goal is to be able to solve the problems formulated above, so this activity is aimed at providing training to improve the welfare of MSMEs. This activity is carried out by: The implementation of this community service activity begins with a problem survey and continues with a coordination meeting with the MSMEs in the Tanah Abang Market, Central Jakarta. This activity ends with an evaluation of the effectiveness of activities by monitoring the business that will be started by each group of MSMEs. The implementation method carried out in this PKM activity is to conduct training by increasing the welfare of MSMEs with sharia concepts through the fields of marketing and finance. This training is also equipped with examples of improving the welfare of MSMEs.